# |
ODE |
Mathematica |
Maple |
\[
{}\left (1+y^{\prime }\right )^{3} = \frac {7 \left (x +y\right ) \left (1-y^{\prime }\right )^{3}}{4 a}
\] |
✓ |
✓ |
|
\[
{}y^{2} \left (1+{y^{\prime }}^{2}\right ) = r^{2}
\] |
✓ |
✓ |
|
\[
{}x {y^{\prime }}^{2}-\left (x -a \right )^{2} = 0
\] |
✓ |
✓ |
|
\[
{}{y^{\prime }}^{2}+2 x y^{\prime }-y = 0
\] |
✓ |
✓ |
|
\[
{}a {y^{\prime }}^{3} = 27 y
\] |
✓ |
✓ |
|
\[
{}x {y^{\prime }}^{2}-2 y y^{\prime }+a x = 0
\] |
✓ |
✓ |
|
\[
{}x^{3} {y^{\prime }}^{2}+x^{2} y y^{\prime }+a^{3} = 0
\] |
✓ |
✓ |
|
\[
{}y^{2}-2 x y y^{\prime }+{y^{\prime }}^{2} \left (x^{2}-1\right ) = m^{2}
\] |
✗ |
✓ |
|
\[
{}y = x y^{\prime }+\sqrt {b^{2}+a^{2} y^{\prime }}
\] |
✓ |
✓ |
|
\[
{}y = x y^{\prime }-{y^{\prime }}^{2}
\] |
✓ |
✓ |
|
\[
{}4 {y^{\prime }}^{2} = 9 x
\] |
✓ |
✓ |
|
\[
{}4 x \left (x -1\right ) \left (x -2\right ) {y^{\prime }}^{2}-\left (3 x^{2}-6 x +2\right )^{2} = 0
\] |
✓ |
✓ |
|
\[
{}\left (8 {y^{\prime }}^{3}-27\right ) x = 12 y {y^{\prime }}^{2}
\] |
✓ |
✓ |
|
\[
{}{y^{\prime }}^{2} \left (-a^{2}+x^{2}\right )-2 x y y^{\prime }+y^{2}-b^{2} = 0
\] |
✓ |
✓ |
|
\[
{}\left (x y^{\prime }-y\right ) \left (x -y y^{\prime }\right ) = 2 y^{\prime }
\] |
✓ |
✗ |
|
\[
{}y+x +x y^{\prime } = 0
\] |
✓ |
✓ |
|
\[
{}\left (x y+1\right ) y-x y^{\prime } = 0
\] |
✓ |
✓ |
|
\[
{}\sin \left (x \right ) y^{\prime }-y \cos \left (x \right )+y^{2} = 0
\] |
✓ |
✓ |
|
\[
{}\left (x +y\right ) y^{\prime }+y-x = 0
\] |
✓ |
✓ |
|
\[
{}x +y y^{\prime }+\frac {x y^{\prime }-y}{x^{2}+y^{2}} = 0
\] |
✓ |
✓ |
|
\[
{}x^{3}+3 x y^{2}+\left (3 x^{2} y+y^{3}\right ) y^{\prime } = 0
\] |
✓ |
✓ |
|
\[
{}x y^{\prime }+y = y^{2} \ln \left (x \right )
\] |
✓ |
✓ |
|
\[
{}\left (-x^{2}+1\right ) y^{\prime }-2 x y = -x^{3}+x
\] |
✓ |
✓ |
|
\[
{}x y^{\prime }-y-\cos \left (\frac {1}{x}\right ) = 0
\] |
✓ |
✓ |
|
\[
{}x +y y^{\prime } = m \left (x y^{\prime }-y\right )
\] |
✓ |
✓ |
|
\[
{}x \cos \left (y\right )^{2} = y \cos \left (x \right )^{2} y^{\prime }
\] |
✓ |
✓ |
|
\[
{}y^{\prime } = {\mathrm e}^{x -y}+x^{2} {\mathrm e}^{-y}
\] |
✓ |
✓ |
|
\[
{}x^{2} y^{\prime }+y = 1
\] |
✓ |
✓ |
|
\[
{}2 y+\left (x^{2}+1\right ) \arctan \left (x \right ) y^{\prime } = 0
\] |
✓ |
✓ |
|
\[
{}x y^{2}+x +\left (x^{2} y+y\right ) y^{\prime } = 0
\] |
✓ |
✓ |
|
\[
{}y^{\prime } = {\mathrm e}^{x +y}+x^{2} {\mathrm e}^{y}
\] |
✓ |
✓ |
|
\[
{}\left (3+2 \sin \left (x \right )+\cos \left (x \right )\right ) y^{\prime } = 1+2 \sin \left (y\right )+\cos \left (y\right )
\] |
✓ |
✓ |
|
\[
{}\frac {\cos \left (y\right )^{2} y^{\prime }}{x}+\frac {\cos \left (x \right )^{2}}{y} = 0
\] |
✓ |
✓ |
|
\[
{}\left (1+{\mathrm e}^{x}\right ) y y^{\prime } = \left (1+y\right ) {\mathrm e}^{x}
\] |
✓ |
✓ |
|
\[
{}\csc \left (x \right ) \ln \left (y\right ) y^{\prime }+x^{2} y^{2} = 0
\] |
✓ |
✓ |
|
\[
{}y^{\prime } = \frac {\sin \left (x \right )+x \cos \left (x \right )}{y \left (2 \ln \left (y\right )+1\right )}
\] |
✓ |
✓ |
|
\[
{}\cos \left (y\right ) \ln \left (\sec \left (x \right )+\tan \left (x \right )\right ) = \cos \left (x \right ) \ln \left (\sec \left (y\right )+\tan \left (y\right )\right ) y^{\prime }
\] |
✓ |
✓ |
|
\[
{}\left (x^{2}-x^{2} y\right ) y^{\prime }+y^{2}+x y^{2} = 0
\] |
✓ |
✓ |
|
\[
{}\left (\sin \left (y\right )+y \cos \left (y\right )\right ) y^{\prime }-\left (2 \ln \left (x \right )+1\right ) x = 0
\] |
✓ |
✓ |
|
\[
{}3 \,{\mathrm e}^{x} \tan \left (y\right )+\left (1-{\mathrm e}^{x}\right ) \sec \left (y\right )^{2} y^{\prime } = 0
\] |
✓ |
✓ |
|
\[
{}-x y^{\prime }+y = a \left (y^{2}+y^{\prime }\right )
\] |
✓ |
✓ |
|
\[
{}\left (x +y-1\right ) y^{\prime } = x +y+1
\] |
✓ |
✓ |
|
\[
{}\left (2 x +2 y+1\right ) y^{\prime } = x +y+1
\] |
✓ |
✓ |
|
\[
{}\left (2 x +3 y-5\right ) y^{\prime }+2 x +3 y-1 = 0
\] |
✓ |
✓ |
|
\[
{}\left (x^{2}+y^{2}\right ) y^{\prime } = x y+x^{2}
\] |
✓ |
✓ |
|
\[
{}\left (x \cos \left (\frac {y}{x}\right )+y \sin \left (\frac {y}{x}\right )\right ) y-\left (y \sin \left (\frac {y}{x}\right )-x \cos \left (\frac {y}{x}\right )\right ) x y^{\prime } = 0
\] |
✓ |
✓ |
|
\[
{}x^{2}-y^{2}+2 x y y^{\prime } = 0
\] |
✓ |
✓ |
|
\[
{}y^{\prime } = \frac {y}{x}+\tan \left (\frac {y}{x}\right )
\] |
✓ |
✓ |
|
\[
{}\left (2 x -2 y+5\right ) y^{\prime }-x +y-3 = 0
\] |
✓ |
✓ |
|
\[
{}x +y+1-\left (2 x +2 y+1\right ) y^{\prime } = 0
\] |
✓ |
✓ |
|
\[
{}y^{2} = \left (x y-x^{2}\right ) y^{\prime }
\] |
✓ |
✓ |
|
\[
{}x \sin \left (\frac {y}{x}\right ) y^{\prime } = y \sin \left (\frac {y}{x}\right )-x
\] |
✓ |
✓ |
|
\[
{}\left (x^{2}+y^{2}\right ) y^{\prime } = x y
\] |
✓ |
✓ |
|
\[
{}x^{2} y^{\prime }+y \left (x +y\right ) = 0
\] |
✓ |
✓ |
|
\[
{}2 y^{\prime } = \frac {y}{x}+\frac {y^{2}}{x^{2}}
\] |
✓ |
✓ |
|
\[
{}\left (6 x -5 y+4\right ) y^{\prime }+y-2 x -1 = 0
\] |
✓ |
✓ |
|
\[
{}\left (x -3 y+4\right ) y^{\prime }+7 y-5 x = 0
\] |
✓ |
✓ |
|
\[
{}\left (2 x +4 y+3\right ) y^{\prime } = x +2 y+1
\] |
✓ |
✓ |
|
\[
{}x y^{\prime }-y = \sqrt {x^{2}+y^{2}}
\] |
✓ |
✓ |
|
\[
{}x \left (x^{2}+3 y^{2}\right )+y \left (y^{2}+3 x^{2}\right ) y^{\prime } = 0
\] |
✓ |
✓ |
|
\[
{}x^{2}+3 y^{2}-2 x y y^{\prime } = 0
\] |
✓ |
✓ |
|
\[
{}y^{\prime } = \frac {2 x -y+1}{x +2 y-3}
\] |
✓ |
✓ |
|
\[
{}\left (x -y\right ) y^{\prime } = x +y+1
\] |
✓ |
✓ |
|
\[
{}x -y-2-\left (2 x -2 y-3\right ) y^{\prime } = 0
\] |
✓ |
✓ |
|
\[
{}y^{\prime }+y \cot \left (x \right ) = 2 \cos \left (x \right )
\] |
✓ |
✓ |
|
\[
{}\cos \left (x \right )^{2} y^{\prime }+y = \tan \left (x \right )
\] |
✓ |
✓ |
|
\[
{}x \cos \left (x \right ) y^{\prime }+\left (x \sin \left (x \right )+\cos \left (x \right )\right ) y = 1
\] |
✓ |
✓ |
|
\[
{}y-\sin \left (x^{2}\right ) x +x y^{\prime } = 0
\] |
✓ |
✓ |
|
\[
{}x \ln \left (x \right ) y^{\prime }+y = 2 \ln \left (x \right )
\] |
✓ |
✓ |
|
\[
{}\sin \left (x \right ) \cos \left (x \right ) y^{\prime } = y+\sin \left (x \right )
\] |
✓ |
✓ |
|
\[
{}\left (1+x +x y^{2}\right ) y^{\prime }+y+y^{3} = 0
\] |
✓ |
✓ |
|
\[
{}y^{2}+\left (x -\frac {1}{y}\right ) y^{\prime } = 0
\] |
✓ |
✓ |
|
\[
{}y^{\prime }+3 x^{2} y = x^{5} {\mathrm e}^{x^{3}}
\] |
✓ |
✓ |
|
\[
{}y^{\prime }-\frac {\tan \left (y\right )}{1+x} = \left (1+x \right ) {\mathrm e}^{x} \sec \left (y\right )
\] |
✓ |
✓ |
|
\[
{}y^{\prime }+\frac {\left (1-2 x \right ) y}{x^{2}} = 1
\] |
✓ |
✓ |
|
\[
{}y^{\prime }+\frac {2 y}{x} = \sin \left (x \right )
\] |
✓ |
✓ |
|
\[
{}1+y^{2} = \left (\arctan \left (y\right )-x \right ) y^{\prime }
\] |
✓ |
✓ |
|
\[
{}1+y+x^{2} y+\left (x^{3}+x \right ) y^{\prime } = 0
\] |
✓ |
✓ |
|
\[
{}y^{\prime }+\frac {x y}{x^{2}+1} = \frac {1}{2 x \left (x^{2}+1\right )}
\] |
✓ |
✓ |
|
\[
{}y^{\prime }+\frac {\tan \left (y\right )}{x} = \frac {\tan \left (y\right ) \sin \left (y\right )}{x^{2}}
\] |
✓ |
✗ |
|
\[
{}y^{\prime }+\frac {y \ln \left (y\right )}{x} = \frac {y}{x^{2}}-\ln \left (y\right )^{2}
\] |
✗ |
✗ |
|
\[
{}y^{\prime }+x = x \,{\mathrm e}^{\left (n -1\right ) y}
\] |
✓ |
✓ |
|
\[
{}y \left (2 x y+{\mathrm e}^{x}\right )-{\mathrm e}^{x} y^{\prime } = 0
\] |
✓ |
✓ |
|
\[
{}2 y^{\prime }-y \sec \left (x \right ) = y^{3} \tan \left (x \right )
\] |
✓ |
✓ |
|
\[
{}y^{\prime }+y \cos \left (x \right ) = y^{n} \sin \left (2 x \right )
\] |
✓ |
✓ |
|
\[
{}x +y y^{\prime } = \frac {a^{2} \left (x y^{\prime }-y\right )}{x^{2}+y^{2}}
\] |
✓ |
✓ |
|
\[
{}1+4 x y+2 y^{2}+\left (1+4 x y+2 x^{2}\right ) y^{\prime } = 0
\] |
✓ |
✓ |
|
\[
{}x^{2} y-2 x y^{2}-\left (x^{3}-3 x^{2} y\right ) y^{\prime } = 0
\] |
✓ |
✓ |
|
\[
{}\left (y^{4} x^{4}+x^{2} y^{2}+x y\right ) y+\left (y^{4} x^{4}-x^{2} y^{2}+x y\right ) x y^{\prime } = 0
\] |
✓ |
✓ |
|
\[
{}y \left (x y+2 x^{2} y^{2}\right )+x \left (x y-x^{2} y^{2}\right ) y^{\prime } = 0
\] |
✓ |
✓ |
|
\[
{}y^{4}+2 y+\left (x y^{3}+2 y^{4}-4 x \right ) y^{\prime } = 0
\] |
✓ |
✓ |
|
\[
{}x^{2}+y^{2}-2 x y y^{\prime } = 0
\] |
✓ |
✓ |
|
\[
{}\left (20 x^{2}+8 x y+4 y^{2}+3 y^{3}\right ) y+4 \left (x^{2}+x y+y^{2}+y^{3}\right ) x y^{\prime } = 0
\] |
✓ |
✓ |
|
\[
{}y^{2}+2 x^{2} y+\left (2 x^{3}-x y\right ) y^{\prime } = 0
\] |
✓ |
✓ |
|
\[
{}2 y+3 x y^{\prime }+2 x y \left (3 y+4 x y^{\prime }\right ) = 0
\] |
✓ |
✓ |
|
\[
{}\frac {x +y y^{\prime }}{x y^{\prime }-y} = \sqrt {\frac {a^{2}-x^{2}-y^{2}}{x^{2}+y^{2}}}
\] |
✓ |
✓ |
|
\[
{}\frac {\left (x +y-a \right ) y^{\prime }}{x +y-b} = \frac {x +y+a}{x +y+b}
\] |
✓ |
✓ |
|
\[
{}\left (x -y\right )^{2} y^{\prime } = a^{2}
\] |
✓ |
✓ |
|
\[
{}\left (x +y\right )^{2} y^{\prime } = a^{2}
\] |
✓ |
✓ |
|
\[
{}y^{\prime } = \left (4 x +y+1\right )^{2}
\] |
✓ |
✓ |
|